One-year study of the efficacy of a dentifrice containing zinc citrate and triclosan to maintain gingival health - Svatun, B; Saxton, C A; Rölla, G; van der Ouderaa, F (Scandinavian journal of dental research, 1989)
In a previous study we demonstrated that gingival health could be maintained in a group of highly motivated nurses using a dentifrice containing a zinc salt and triclosan. We have now investigated the effect of the experimental dentifrice on a group of less motivated men. One hundred and three male students were given oral hygiene instruction (OHI) and their teeth were professionally cleaned. For each individual, both the instruction and cleaning were completed in a single 15-min period. Two balanced groups were formed, based on the prestudy plaque levels and gingival bleeding. One group used the experimental dentifrice for 12 months, while the other used a control. Results were assessed after 6 months, and after 12 months. As a result of the OHI, plaque and gingival bleeding were reduced at the end of the prestudy period. This improvement was not maintained by the control group even for 6 months. In contrast, the test group exhibited significantly lower plaque levels and higher standard of gingival health throughout the 12 months. Reassessment of available participants 6 months after the study showed that gingival health in both groups had returned to its prestudy condition. The lower observed standard of gingival health in the test group after ceasing to use the experimental dentifrice further supports the conclusion that this dentifrice can contribute to an oral care program.